Reference values of cardio-ankle vascular index in a random sample of a white population - Wohlfahrt, Peter; Cífková, Renata; Movsisyan, Narine; Kunzová, Šárka; Lešovský, Jiří; Homolka, Martin; Soška, Vladimír; Dobšák, Petr; Lopez-Jimenez, Francisco; Sochor, Ondřej (Journal of hypertension, 2017)
OBJECTIVES: Cardio-ankle vascular index (CAVI), a parameter of arterial stiffness, has been increasingly used for cardiovascular risk estimation. Currently used CAVI reference values are derived from the Japanese population. It is not clear whether the same reference values can be used in the white population. The aim of the present study was to describe cardiovascular risk factors influencing CAVI and to establish CAVI reference values. METHODS: A total of 2160 individuals randomly selected from the Brno city population aged 25-65 years were examined. Of these, 1347 patients were free from cardiovascular disease, nondiabetic and untreated by antihypertensive or lipid-lowering drugs, forming the reference value population. CAVI was measured using the VaSera VS-1000 device (Fukuda Denshi, Tokyo, Japan). RESULTS: At each blood pressure (BP) level, there was a quadratic association between CAVI and age, except for a linear association in the optimal BP group. Although there was no association between BP and CAVI in younger patients, there was a linear association between CAVI and BP after 40 years of age. Reference values by age and sex were established. In each age group, except for the male 60-65-year group, reference values in our population were lower than in the Japanese one with the difference ranging from -0.29 to 0.21 for men, and from -0.38 to -0.03 for women. CONCLUSION: This is the first study providing CAVI reference values in a random sample of the white population. Our results suggest that the currently used values slightly overestimate CAVI in younger white, possibly underestimating cardiovascular risk.
Keywords: dospělí; Female; Age Factors; Adult; ženské pohlaví; věkové faktory; lidé; tlakový index kotník-paže; kotník; Ankle Brachial Index; referenční hodnoty; krevní tlak; rychlost toku krve; Blood Flow Velocity; Middle Aged; Risk Factors; Male; Cardiovascular Diseases; Aged; Czech Republic; Reference Values; Blood Pressure Determination; rizikové faktory; kardiovaskulární nemoci; Česká republika; měření krevního tlaku; lidé středního věku; senioři; mužské pohlaví; White People; Blood Pressure; běloši; Ankle; Humans